Development of a Sustainability Model for Muslim SMEs in West Java: An Analysis of the Integration between the Triple Bottom Line and Islamic Economic Principles - Sudana, Sudana; Awaludin, Latief; Dermawan, Muhammad Jagat; Samudra, Muhammad Gilang; Andika, Galih Pribadi (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This study develops a sustainability model for Muslim SMEs in West Java by integrating the Triple Bottom Line (TBL) and Islamic Economic principles. TBL covers financial, social, and environmental aspects. A qualitative method with a phenomenological approach is used. Data were collected through interviews and analyzed using NVivo. Findings show that Muslim SMEs in West Java prioritize financial and social aspects, with limited attention to the environment. From an Islamic Economic perspective, sustainability includes environmental responsibility as a mandate. Financial practices involving riba, maysir, and gharar increase financial risks and social tensions. The proposed sustainability model integrates TBL and Islamic principles. The key contribution is a model based on Islamic values that guides Muslim SMEs in adapting TBL within a Sharia-compliant framework. This model reduces dependence on riba-based financing, enhances community empowerment, and strengthens environmental management in line with Islamic principles.